2010
DOI: 10.1002/cphc.200900772
|View full text |Cite
|
Sign up to set email alerts
|

Exclusively Heteronuclear NMR Experiments to Obtain Structural and Dynamic Information on Proteins

Abstract: Provided that (13)C-detected NMR experiments are either preferable or complementary to (1)H detection, we report here tools to determine C(alpha)-C', C'-N, and C(alpha)-H(alpha) residual dipolar couplings on the basis of the CON experiment. The coupling constants determined on ubiquitin are consistent with the subset measured with the (1)H-detected HNCO sequences. Since the utilization of residual dipolar couplings may depend on the mobility of the involved nuclei, we also provide tools to measure longitudinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 94 publications
(117 reference statements)
1
30
0
Order By: Relevance
“…The prediction that the WIP N fragment is disordered was confirmed by its CD curve and NMR fingerprint spectra. Nevertheless, in this study well established 13 C-detected experiments [22,62] [53] and are able as shown here to identify regions of transient structure. The interpretation of RDCs for IDPs under anisotropic conditions is challenging, since normally a folded structure is required for analysis of such data.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The prediction that the WIP N fragment is disordered was confirmed by its CD curve and NMR fingerprint spectra. Nevertheless, in this study well established 13 C-detected experiments [22,62] [53] and are able as shown here to identify regions of transient structure. The interpretation of RDCs for IDPs under anisotropic conditions is challenging, since normally a folded structure is required for analysis of such data.…”
Section: Discussionsupporting
confidence: 64%
“…RDCs were calculated by subtracting couplings determined in a standard sample (vide supra) from those obtained in the anisotropic sample. Ca) couplings were based on an (HACA)CON experiment in which the measured coupling was allowed to evolve during a fraction of the 15 N evolution time (typically 33-50%) [62]. A CON-IPAP lacking 1 H decoupling during 15 N evolution was sufficient for measuring the 1 latter experiment to avoid amide proton exchange with solvent which tends to broaden the cross-peaks in exposed regions.…”
Section: Acquisition Of Nmr Datamentioning
confidence: 99%
“…One method to combat this collapse is to encode longer range sequence into the spectra (Nováček et al 2014), where the resulting high dimensional spectra are approximated with non-uniform sampling methods. Another method to com-bat collapsed spectra is the use of 13 C detection instead of 1 H detection (Bermel et al 2006). Detection of 13 C can separate resonances by a factor of 3 compared to detection of 1 H. Additionally, 13 C is not sensitive to exchange broadening or as sensitive to salt concentration as 1 H, which can further improve spectra taken near physiological conditions (Gil et al 2013;Felli and Pierattelli 2014;Nováček et al 2014;Chap. 3).…”
Section: Developing Improved Methods For the Study Of Idps By Nmrmentioning
confidence: 99%
“…Since 1 H polarization is only used as a starting source to enhance the sensitivity of the exclusively heteronuclear experiments, this enables us to easily control the state of 1 H polarization and to manipulate selectively different sets of spins, thus providing a valuable tool to determine observables involving 1 H nuclear spins. [33][34][35] To expand the range of applications of exclusively heteronuclear experiments for the characterization of disordered proteins we decided to focus on amide proton exchange rates with the solvent and on 1 H- 13 C NOEs as they provide information to characterize the solvent accessibility and the local flexibility of the polypeptide, two parameters usually considered diagnostic for characterizing unfolded protein states. The details of pulse sequence design, the experimental results as well as the kind of information that can be obtained are described in the following sections.…”
Section: Characterization Of Intrinsically Disordered Proteinsmentioning
confidence: 99%